IN REFERENCE TO THE RESEARCH OF PIPE BELT CONVEYOR - Sazambayeva, B.T.; Samogin, Y.N.; Togizbayeva, B.B.; Kassymbekov, Zh.; Makhanov, M.; Dzhudibayev, V.E.; Kinzhebayeva, A.S. (Scientific Journal of Pedagogy and Economics, 2020)
The article considers the initial provisions of the research and design of conveyor transport that allows to transport bulk cargo in safety. At the same time, it is noted that there is a need for a harmless impact on the environment, especially in long-distance routes transporting with vertical and horizontal bends, as well as with a minimum number of reloading nodes. The review and analysis of the standard sizes of existing conveyors shows certain advantages of the technological nature of the pipe belt conveyor (PBC). The considered construction of PBC, in comparison with existing ones is formed with a closed belt tray due to support devices placed along the perimeter of the transportation line of bulk cargo. It is indicated that when the belt with the load moves simultaneously behind the roller support, due to some collapse of the belt the relationship between the cargo particles and the belt decreases and the system "transported cargo – conveyor belt" is in an active stress state. This circumstance makes it possible to ignore the active phase at high transport speeds. It is revealed that the main advantages of conveyor transport are a high level of labor productivity, achieved by automating the operation of equipment and low production costs. The problems are the need to split the transported cargo, accurate reconciliation of transition areas, coordination of drives and synchronization of movements, easily adjustable in the course of work, subject to certain initial construction conditions. The tractive calculation of the PBC by circumventing the contour, as with traditional conveyors, allowed us to determine the force of resistance to the movement of the belt, the load pressure along the cross section, and the forces acting on the lower and side rollers. A computer 3D model of the PBC was created by using the SolidWorks software product, which includes: creating special support elements and roller supports that twist the belt into the pipe, selecting metal construction elements and calculating their strength, roller supports, and supporting conveyor devices. The stress-strain state of the belt is shown and a model of the PBC under load is constructed, a load map that allows analyzing the distribution of various internal reactive force factors, i.e. forces and moments that occur in the elements of the design model.